Covid-19 Anthropology: Tagline Analysis “Banyuwangi Rebound” - Andang Subaharianto (International Publisher (YAPENBI), 2022)
The condition of the Covid-19 pandemic is of course the background and the reason. The pandemic has clearly hit the economy (Marpaung, Adrian, and Putri 2020). It spreads to other aspects of life as well. Not only local, regional, or national, even global. Heavy and not easy. The government is forced to manage its resources and focus on the impact of the pandemic. The local government of Banyuwangi Regency is no exception. Resources are forced to be directed, refocused on dealing with the impact of the pandemic. The public awaited Ipuk Fiestiandani and Deputy Regent Sugirah. Both his presence and his ideas. Understandably, people are concerned, anxious, suffering, and even almost desperate. Due to the ongoing Covid-19 pandemic. The Regent called Banyuwangi Rebound. To mark his leadership krida. The regent seems serious. The Banyuwangi Rebound slogan then adorned the banners and stage backdrops for Banyuwangi Regency government activities. Banyuwangi Rebound then became the keyword. People started to talk about it. This Writing Method Is Descriptive. We all learn from the pandemic. From difficult situations and conditions. From the perspective of liminality, the pandemic should produce innovations in the outer and inner systems, especially with regard to the way humans fulfill their needs. Like it or not, like it or not, Regent Ipuk and Deputy Regent Sugirah must step up. You have to choose where to go. Ipuk believes that the pandemic will not end soon. The pandemic will still suck up resources. What must be overcome is not only the economy, but the impact of the economic downturn and a number of counter-pandemic views. Like it or not, like it or not, policies and programs.